Shaping the Investment Decision of Young Investors in China: Behavioural Factors and Effect of Trust - JinMei, Duan; Choong, Yap Voon; Aravindan, Kalisri Logeswaran; Muthaiyah, Saravanan; Yee, Pook Sow (Journal of Posthumanism, 2025)
Purpose – The objective of this study is to explore the key elements influencing decision- making processes among young individuals in China. The selected factors are emotional intelligence, herd behaviour, overconfidence, accounting information and financial literacy. In addition, this study aims to examine whether trust acts as a mediating factor between these factors and investment decision making. Methodology – This study employed an online survey questionnaire distributed to young investors in Shenzhen aged between 30 and 42 years. The questions were modified from prior studies, and responses were collected through a 5-point Likert-type scale. G*Power was employed for calculating the minimum sample size, resulting in at least 500 useable responses. A total of 507 surveys was distributed, of which 504 responses were utilised. For data analysis, PLS-SEM was employed in this study as it is suitable for handling complex model and exploratory research. Findings – All the variables are supported. Emotional intelligence, accounting information and financial literacy are positively correlated, whereas herd behaviour and overconfidence are negatively correlated. In addition, trust acts as a positive mediating factor in these relationships, except in the case of herd behaviour and overconfidence. Practical implications – Retail and corporate investors can be aware of their behavioural biases and control their emotions to make rational decisions. The government can foster a better understanding of investor behaviour and formulate the necessary policies to stimulate and stabilise the economy.